Effect of practical application of intimate relationship skills program in marital commitment of couples - Bahareh Chitsazzadeh Alaf; kianoush zahrakar; Bagher Sanai (Gonabad University of Medical Sciences, 2017)
Nowadays, due to the increasing rate of divorce and betrayals, the marital commitment has been concerned in marriage and family studies. The research aimed to evaluate the effect of Practical Application of Intimate Relationship Skills (PAIRS) program in marital commitment of couples. The method was quasi-experimental and the design was pretest-posttest with a control group. The convenience sampling method was employed to choose 16 couples whose marital commitment score was below the mean in Isfahan, Iran. These couples were randomly assigned to the experimental and control groups (N=8 in each group). Data gathering was carried out using Adams and Jones dimensions of commitment inventory (DCI) that was filled out by the members of both groups in the pretest stage. Then, the experimental group received the PAIRS training program in thirteen 90-minute sessions. 35 percent of the total variance belongs to the group membership due to the effectiveness of this educational program. This educational program attempts to make couples aware of themselves and their spouses, enhance, intimacy and empathy and develop effective relationship skills and problem-solving skills. The results demonstrated that the PAIRS program showed a positive effect on marital commitment. Hence, the PAIRS program can be employed to prevent divorce by increasing marital commitment in couples.